Anterior knee swelling in severe knee osteoarthritis - co-existence of intra and extra-articular synovial chondromatosis within quadriceps muscle and suprapatellar bursae: An uncommon presentation - Nur Azree Ferdaus, Kamudin; Rizal, Ab Rani; Nor Hamdan, Mohamad Yahaya (2019)
Synovial chondromatosis is a benign condition found in the knee (up to 70%), followed by the hip, elbow, wrist, and shoulder joints. It has a rare incidence of 1 per 100 000 people. We report a case of a 68-years-old lady who presented with progressive left knee pain for the past two years associated with a swelling of the knee, which later migrated proximally to the distal thigh. The patient did not notice any increase in size but complained of pain especially in the extended knee position. Physical examination showed bilateral genu varus, and the right knee lateral collateral ligament laxity with tenderness over the medial joint line. Range of motion knee was 5 to 90O . The lesion was a 4 x 3cm hard non-tender swelling with a well-defined border localized to the anterior thigh distally. It was mobile and moves with quadricep muscles contraction. Radiological imaging showed knee osteoarthritis grade 4 with congregations of multiple calcified nodules located in the thigh with solitary intra-articular calcified nodular mass. Intra-operatively, there were multiple lesions of different sizes found within the quadriceps muscle. Total knee replacement was performed, and tissue samples were sent for histopathological examination which was later reported as synovial chondromatosis with no evidence of malignancy. This case report highlights the even rarer presentation of extra-articular synovial chondromatosis located within the quadriceps and superficial to the patellar bursae. Post-operatively, the patient was “pain free” and there was no recurrence of the lesion at one year follow up.